THE INTEGRATION OF EDUCATION IN MULTI-RACIAL AND MULTI-CULTURAL SOCIETY - Chamisah Chamisah; Ridhwan M. Daud (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
This study aims to know the reasons of education ina multi-racial and multi-cultural society demands integration.. The studywhich focuses onMalaysia country typified by three major ethnic groups, namely Malays, Chinese and Indians,foundthat, firstlythe integration of curriculum in creating a holistic education isvital for the society to create a competitive human capital with value laden such as trustworthiness, dedication, creativity, civic awareness and many more. Secondly, integration curriculum emphasizes on the equity and equality of education for all.Through interacting with individuals from a range of religious and ethnic backgrounds, people will learn to understand, accept and embrace differences. Throughsharing experiences and aspirations,a common national identity and ultimately unity can be achieved. Therefore, integrating curriculum is not only to integrate Islamic concepts in the education system but alsoto integrate all the concepts that make one comprehensive curriculum. Thirdly, it is important to integrate the curriculum with a value-laden perspective to encourage solidarity and harmony. Keywords: Multi-racial; Multi-cultural society; Education; Malaysia